2008
DOI: 10.1007/s11434-007-0516-2
|View full text |Cite
|
Sign up to set email alerts
|

Meanders of the Jialing River in China: Morphology and formation

Abstract: As a fundamental category of river system, comparisons in diverse regions and types with quantitative parameters on meander morphology will help to distinguish different characteristics and approach formations and evolutions. It also can provide scientific basis of geomorphology for their protections and exploitation of the meander resources. Based on the images of Google Earth, meanders' parameters are proposed and then measured and calculated. The result suggests that incised meanders in the Jialing River ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…2a and 3b ). The distribution boundary for the Mishmi and Bhutan subspecies is most likely the Yalu Zangbu River, which also stemmed from the collision of the Indian and Eurasian Plates and formed in the early Miocene ( Wang et al 2002 ), and that for the Sichuan and Qinling subspecies is most likely the Jialing River that was built in the middle Pleistocene ( Zhang et al 2008 ), as suggested by the genomic findings ( figs. 2a and 3b ).…”
Section: Resultsmentioning
confidence: 93%
“…2a and 3b ). The distribution boundary for the Mishmi and Bhutan subspecies is most likely the Yalu Zangbu River, which also stemmed from the collision of the Indian and Eurasian Plates and formed in the early Miocene ( Wang et al 2002 ), and that for the Sichuan and Qinling subspecies is most likely the Jialing River that was built in the middle Pleistocene ( Zhang et al 2008 ), as suggested by the genomic findings ( figs. 2a and 3b ).…”
Section: Resultsmentioning
confidence: 93%
“…However, based on the geological background, hydrodynamic force, and complex boundary conditions in a wide region, the river morphology is so complex that the coefficient of sinuosity is always high. Based on the symmetry index, the gullies can also be divided into left skewed, symmetric, and right skewed types (Zhang et al, 2008). Further exploration is still necessary with regard to classifying the gully morphology based on the shape ratio, morphology ratio, and fractal dimension, or based on multiple parameters from comprehensive and quantitative perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…The river pattern is usually controlled by factors such as geological structure, strata, lithology, and topographical conditions (Zhang et al, 2008). From the river head to the estuary, these conditions change greatly, and thus the river morphology usually shows very great differences along its course.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the effects of mesh resolution and the Manning coefficient, the difference between the computed and surveyed water levels is acceptable. Additionally, due to river bed evolution, the topography used in the numerical model may be different from the topography in 1990 and this may be the reason for the difference [32]. Generally, the numerical model developed was validated to be accurate enough for further study.…”
Section: Validation Of the Numerical Modelmentioning
confidence: 99%